Komunikacja według innych miar szyta… Porozumiewanie się z seniorami w opinii ludzi młodych - Rosińska-Mamej, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The article presents obstacles (barriers) indicated by young people that make communication with seniors difficult. The author discusses selected cognitive phenomena (e.g. cognitive disharmony, features of the senile mentality) and some problems concerning language and communication (e.g. indistinct articulation) as well as seniors’ hearing difficulty, all contributing to the deterioration of message reception.